2013
DOI: 10.1097/qai.0b013e318285d449
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Mogen Clamp Versus Plastibell for Neonatal Male Circumcision in Botswana

Abstract: Background Male circumcision can reduce the risk of heterosexually-acquired HIV-1 infection in men. Neonatal male circumcision (NMC) has many potential advantages over circumcision at older ages but little is known about its feasibility and safety in resource-limited settings. Methods We performed a randomized trial in southeastern Botswana of Mogen clamp and Plastibell, two commonly used devices for NMC. Follow-up visits occurred at six weeks and four months postpartum. Adverse events, parental satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 22 publications
6
43
1
2
Order By: Relevance
“…However, our morbidity risk was lower than the three published African studies conducted in large urban hospitals in Nigeria and Botswana. These studies reported a 18% (range 10–24%) risk of morbidity 6–16 weeks post‐infant male circumcision . The case definitions used in those studies were similar to our study.…”
Section: Discussionsupporting
confidence: 85%
“…However, our morbidity risk was lower than the three published African studies conducted in large urban hospitals in Nigeria and Botswana. These studies reported a 18% (range 10–24%) risk of morbidity 6–16 weeks post‐infant male circumcision . The case definitions used in those studies were similar to our study.…”
Section: Discussionsupporting
confidence: 85%
“…96-99 The study builds on work from an ongoing study of the Botswana-Harvard AIDS Institute Partnership in Mochudi, a community of 40,000 persons in Botswana. 100-105 PEPFAR and the BMGF have subsequently sponsored a harmonization effort between the HPTN 071(PopART) study and the Botswana Combination Prevention Project that shares similar goals as those of HPTN 071(PopART), but has a different study design.…”
Section: Other Population-level Combination Prevention Studiesmentioning
confidence: 99%
“…After a ''catch-up'' period of circumcising adolescent and adult males who are at highest risk of acquiring HIV in the short term, several governments including the Government of Kenya, intend to scaleup EIMC for cost-efficient HIV prevention ( Ref 11]. EIMC studies and/or service provision have begun in Botswana, Kenya, Lesotho, Swaziland, Uganda, Zambia and Zimbabwe ( Ref 8,[12][13][14][15][16]. Previous acceptability studies have indicated several common barriers to EIMC services in east and Southern Africa including: fear of pain, bleeding, death and other adverse events associated with the procedure, and cultural opposition to EIMC ( Ref 17].…”
Section: Introductionmentioning
confidence: 99%